Novel One-Pot Synthesis of 3,4-dihydropyrimidin-2(1H)-ones and 3,4,7,8- tetrahydroquinazoline-2,5-diones Using Pyridinium p-toluenesufonate as Catalyst - Amine Khodja, Imene; Boulcina, Raouf; Debache, Abdelmadjid (Letters in Organic Chemistry, 2015)
A mild, simple and efficient procedure for the preparation of 3,4-dihydropyrimidin-2(1H)-ones and 3,4,7,8- tetrahydroquinazoline-2,5-diones is described using pyridinium p-toluenesufonate as an efficient catalyst under mild conditions. Simple methodologies, easy work-up procedure, excellent yields and very short reaction times are among the other advantages of this work.
Keywords: 4